Donas das dores no laço da verdade: violências contra mulheres trabalhadoras nos quadrinhos - Sousa, Karine Freitas (2017)
Women’s representations in the media and arts show images and languages which associated to violence contribute to the conservation of stereotypes and perpetuate the sexist culture. Some professionals / workers in comics suffered moral, psychological, emotional and physical harassment which were allowed in the fictional world by the use of trivialities, jokes and poetic license. This thesis detects violence against women characters, secretaries in comics in tessitura with feminism. It also establishes how the sexual relations occur in the so called “women profession” even in the comics, as well as how the relations are reflected in the collective mentalities of the Patriarchy that provide and also keep the gender inequalities in a subordinate status